Can rove beetles (Staphylinidae) be excluded in studies focusing on saproxylic beetles in central European beech forests?. Issue 1 (1st December 2014) - Parmain, G.; Bouget, C.; Müller, J.; Horak, J.; Gossner, M.M.; Lachat, T.; Isacsson, G.
Abstract Monitoring saproxylic beetle diversity, though challenging, can help identifying relevant conservation sites or key drivers of forest biodiversity, and assessing the impact of forestry practices on biodiversity. Unfortunately, monitoring species assemblages is costly, mainly due to the time spent on identification. Excluding families which are rich in specimens and species but are difficult to identify is a frequent procedure used in ecological entomology to reduce the identification cost. The Staphylinidae (rove beetle) family is both one of the most frequently excluded and one of the most species-rich saproxylic beetle families. Using a large-scale beetle and environmental dataset from 238 beech stands across Europe, we evaluated the effects of staphylinid exclusion on results in ecological forest studies. Simplified staphylinid-excluded assemblages were found to be relevant surrogates for whole assemblages. The species richness and composition of saproxylic beetle assemblages both with and without staphylinids responded congruently to landscape, climatic and stand gradients, even when the assemblages included a high proportion of staphylinid species. At both local and regional scales, the species richness as well as the species composition of staphylinid-included and staphylinid-excluded assemblages were highly positively correlated. Ranking of sites according to their biodiversity level, which either included or excluded Staphylinidae in species richness, also gave congruent results. From our results, species assemblages omitting staphylinids can be taken as efficient surrogates for complete assemblages in large scale biodiversity monitoring studies.